Preparation of monodisperse porous silica particles using poly(glycidyl methacrylate) microspheres as a template - Grama, S; Horák, Daniel (Physiological research, 2015)
Monodisperse macroporous poly(glycidyl methacrylate) (PGMA) microspheres were used as a template for preparing porous silica particles. The starting polymer microspheres that were 9.3 microm in size were synthesized by multistep swelling polymerization using a modified Ugelstad technique. Subsequently, silica (SiO2) was deposited on the surface and inside the PGMA microspheres to produce poly(glycidyl methacrylate)-silica hybrid particles (PGMA-SiO2). Upon calcination of the PGMA-SiO2 microspheres, porous silica particles were formed. The morphology, particle size, polydispersity and inner structure of the silica microspheres were investigated by scanning and transmission electron microscopy. Thermogravimetric analysis and dynamic adsorption of nitrogen determined the amount of silica formed and its specific surface area. Compared with the starting PGMA microspheres, the size of the porous silica particles decreased by up to 30%. These porous silica microspheres are promising for chromatography and biomedical applications.
Keywords: oxid křemičitý; kyseliny polymethakrylové; Nanoparticles; poréznost; Polymethacrylic Acids; Porosity; velikost částic; Silicon Dioxide; Thermogravimetry; Microspheres; termogravimetrie; Nitrogen; mikrosféry; dusík; nanočástice; Particle Size